Extent of surgery did not affect recurrence during 7‐years follow‐up in papillary thyroid cancer sized 1‐4 cm: Preliminary results. (18th April 2017) - Kim, Min Joo; Lee, Myung‐Chul; Lee, Guk Haeng; Choi, Hoon Sung; Cho, Sun Wook; Kim, Su‐jin; Lee, Kyu Eun; Park, Young Joo; Park, Do Joon
Summary: Objective: There is debate whether hemithyroidectomy is sufficient for patients with papillary thyroid cancer (PTC) sized 1‐4 cm. Therefore, we investigated whether hemithyroidectomy affects recurrence rate compared with thyroidectomy in patients with PTC sized 1‐4 cm. Design: Retrospective observational study. Patients: We included 147 patients with 1‐4 cm PTC who underwent hemithyroidectomy between 2004 and 2008. They were matched with 298 patients who underwent thyroidectomy, comparing age, sex, tumour size, multiplicity, extrathyroidal extension status and lymph node (LN) metastasis status. Measurements: Recurrence‐free survival (RFS) was compared between hemithyroidectomy and thyroidectomy groups. Results: Median follow‐up length was 7 years, during which there were nine (6.1%) and 17 (5.7%) recurrences in hemithyroidectomy and thyroidectomy groups, respectively. Recurrence‐free survival in the hemithyroidectomy group was not different from that in the thyroidectomy group regardless of variant, multifocality, LN metastasis and radioactive iodine treatment. However, in subgroup analysis, hemithyroidectomy significantly increased the risk of recurrence in patients with contralateral nodules on the preoperative imaging. Conclusions: Recurrence after hemithyroidectomy was not different from that after thyroidectomy during a median follow‐up of 7 years. However, because thyroidectomy might be favoured in patients with contralateral nodules at preoperative evaluation, a thorough evaluation of the contralateral thyroid lobe is necessary.